a) ( x - 45 ) . 27 = 0
( x - 45 ) = 0 : 27
( x - 45 ) = 0
x = 0 + 45
x = 45
b) 23 . ( 42 - x ) = 23
( 42 - x ) = 23 : 23
( 42 - x ) = 1
x = 42 - 1
x = 41
\(\text{Ta có: (x - 45).27 = 0
}\)
\(\text{ x - 45 = 0 : 27
}\)
\(\text{ x - 45 = 0
}\)
\(\text{ x = 0 + 45
}\)
\(\text{ x = 45}\)
a) (x-45).27=0
=>x-45=0
=>x=0+45
=>x=45
b)23.(42-x)=23
=>42-x=23:23
=>42-x=1
=>x=42-1
=>x=41
a) (x - 45 ) . 27 = 0
( x - 45 ) = 0 : 27
( x - 45 ) = 0
x = 45 + 0
x = 45
b) 23 . ( 42 - x ) =23
( 42 - x ) = 23 : 23
( 42 - x ) = 1
x = 42 - 1
x = 41